Predicting the product particle size distribution from a laboratory vertical stirred mill. (December 2018) - Rocha, Danielle; Spiller, Erik; Taylor, Patrick; Miller, Hugh
Highlights: Changes in agitator speed and grinding media size mainly affect the particle breakage rate. A finer product size is obtained when the mill operates at highest stirrer speed and using the smaller grinding media. The final product particle size distribution is directly dependent on the breakage environment promoted by the equipment. Good data agreement in terms of product size was obtained when using a Bond ball mill to predict the final product size distribution from the vertical stirred mill. Abstract: The use of ball mills for fine grinding is inefficient resulting in an increasing use of vertical stirred mills in the mineral processing industry. The difficulty encountered in fine grinding is the increased resistance to comminute small particles compared to coarse particles. Therefore, increased energy inputs are necessary to raise the number of stress events in a mill to contribute to the comminution of the fine material. In this study, a research program was designed and carried out to predict the performance of a laboratory scale vertical stirred mill. An energy-based population balance model was developed to analyze the response in product size by changing operating conditions. The model prediction was compared with the results obtained in the laboratory vertical stirred mill. The grinding results show that changes in feed size, agitator speed, and grinding media size mainly affect the particle breakage rate. The test data also show that a finer product size is obtained when the mill operates at higher stirrer speed and when using smaller grinding media.